Edge of spider-verse (2023) ebook Bleeding edge. - Slott, Dan (Edge of Spider-Verse (2023), 2024)
Collects Edge of Spider-Verse (2023) #1-4. Over the edge! Journey across the Spider-Verse once again with a spectacular mix of fan-favorite and all-new spider-heroes! Spider-Rex is back to face the Venomsaurus! But who is the Spider-Killer?! Only the scariest spider-character ever created! The all-singing, all-swinging sensation Spinstress croons her way into the biggest fight of her life! And the dark future of the Empire of the Spider, last seen in MILES MORALES: SPIDER-MAN, still needs a hero - and here comes Miles' little sister, Billie Morales, all-grown up as Spider-Smasher! Plus: The amazing origin of the breakout character introduced in the pages of SPIDER-MAN #7 - make way for Spider-Boy! The return of Dream-Spider from DEADLY NEIGHBORHOOD SPIDER-MAN! And what if the radioactive spider we all know and love had bitten…J. Jonah Jameson?!